P2_3 Electric Armour - Phillips, Mark; Herlingshaw, Katie; Vasudevan, Duleep; Griffiths, Thomas (Physics Special Topics, 2014)
The validity of using a highly charged capacitor as ‘electric armour’ on light tanks is investigated. The capacitor discharges a large amount of energy into the incoming projectile, causing it to vaporise. It is found that a potential difference of 1kV is required to charge the capacitor to the desirable electric potential energy to vaporise the projectile.